Enantioselective alpha-Alkylation of Benzylideneamino tert-Butyl Malonates by Phase-Transfer Catalysis - Park, Cheonhyoung; Ha, Min Woo; Kim, Byungsoo; Hong, Suckchang; Kim, Doyoung; Park, Yohan; Kim, Mi-hyun; Lee, Jae Kyun; Lee, Jeeyeon; Park, Hyeung-geun (WILEY-V C H VERLAG GMBH, 2015)
A new enantioselective synthetic method for the synthesis of alpha,alpha-dialkylmalonates with a quaternary carbon center was developed via alpha-alkylation of prochiral malonates by phase-transfer catalysis (PTC). Asymmetric alpha-alkylation of benzylideneamino tert-butyl alpha-methylmalonates under phase-transfer catalytic conditions in the presence of (S,S)-3,4,5-trifluorophenyl-NAS bromide afforded the corresponding alpha,alpha-dialkylmalonates in high yields (up to 97%) with excellent enantioselectivities (up to 98% ee). The products were then selectively hydrolyzed to chiral malonic monoacids under basic, acidic, or catalytic hydrogenation conditions.
Keywords: ASYMMETRIC ALKYLATION; STEREOSELECTIVE-SYNTHESIS; 1,3-DICARBONYL COMPOUNDS; CONJUGATE ADDITION; MICHAEL ADDITIONS; CARBON CENTER; AMINO-ACIDS; CONSTRUCTION; DESYMMETRIZATION; FLUORINATION